Answer:
2
Step-by-step explanation:
The general term of an arithmetic sequence is given by the explicit formula ...
an = a1 +d(n -1)
The first term is a1 = -4, and the 8th term is a8 = 10. Using these numbers in the formula, we find ...
a8 = a1 +d(8 -1) . . . . put n=8 into the formula
10 = -4 + 7d . . . . . . . fill in the other known values
14 = 7d . . . . . . . . . . . add 4
2 = d . . . . . . . . . . . . . divide by 7
The common difference is 2.
_____
You may have noticed that the difference between the first and eighth terms is 8-1 = 7 times the common difference. And, our solution is ...
d = (10 -(-4))/7 = 2